Analysis and Information Needs for Fisheries Production with Freshwater Aquaculture - Prabhat Ranjan (Research Parks Publishing LLC, 2020)
The big water bodies covering about 4.3 metres hectare of inland water and 480 km of coastline give very high potential for fisheries and aquaculture production, the subtropical climate and adequate soil and aquatic conditions. Despite this, the development of fish remained very poor and stagnant until 1985. Owing to a lack of funding for science, the few development projects introduced at the time did not achieve the desired results. Consequently , the second and third five year plans did not meet the production goals stated. On the other hand, in 1984 the FRI was developed and improved aquaculture and management practises were subsequently produced, and a positive contribution was made to almost reaching the production target of 1.2 m tonnes, in 1994-95, the final year of the Fourth Five Year Plan.The aquaculture sector in India is a rapidly growing, more than 7 per cent, fish farming sector annually. About 95% of total annual aquaculture production of 5.77 million tonnes is supported by Freshwater Aquaculture. The three main Indian carps (CatlaCatla, Labeorohita and Cirrhinusmrigala) and their